6 - Africa’s Developmental Impasse: Some Perspectives and Recommendations - Dembele, Demba Moussa (Africa Development, 2021)
Africa is among the “poorest” regions of the world. The reality is that Africa is not poor but rather impoverished. This impoverishment dates back to the dawn of capitalism when slavery was one of the key elements of capitalism’s “original accumulation”, as demonstrated par Karl Marx in The Capital. Colonial administration replaced slavery as from the 19th Century with the occupation of Africa by Western powers. This has led to a systematic looting of its natural resources and the exploitation of its cheap labour which served to industrialise Western countries. Thus, slavery and colonisation constituted the main causes of Africa’s impoverishment. With its accession to independence from the 1960s, one may have thought that looting Africa would have come to an end and its development stepped up. It was the contrary that occurred because in many countries, foreign domination had been reinforced in connivance with the new African leaders. The failure of the neo-colonial management of African countries was illustrated by the external debt crisis which started from the end of the 1970s and led to the World Bank and IMF’s intervention. These institutions forced upon African countries the notoriously sad adjustment programmes which contributed to worsening the crisis in their economies, taking poverty to an unprecedented level. The international financial crisis that occurred in 2008 illustrated the failure of market fundamentalism of which adjustment programmes are the forerunners. This crisis which has shaken the very bases of the capitalistic system affords African leaders and thinkers the opportunity to break loose of the neoliberal yoke and explore a development path that is more in tune with Africa. The author underscores that such a path should be non-capitalistic because the heavy toll that Africa has paid since the birth of capitalism until now is a proof that the capitalistic development model is bound to fail. Socialism is the most appropriate development option because it can reconcile economic efficiency, wealth redistribution, social justice and democracy.